OCT Angiography Assessment of Type 1 Diabetes Mellitus Patients Without Diabetic Retinopathy: A 3-Year Follow-Up Study - Alexandra Oltea Dan; Carmen Luminița Mocanu; Alin Ștefan Ștefănescu-Dima; Andreea Cornelia Tănasie; Veronica Elena Maria; Anca Elena Târtea; Andrei Theodor Bălășoiu (Diagnostics, 2025)
Background/Objectives: This study aims to investigate the progression of retinal microvascular changes using OCTA in young T1DM patients without clinical signs of DR over a period of 3 years. Methods: This prospective, longitudinal study analyzed OCT angiograms of T1DM patients without clinical signs of DR. It included 40 T1DM patients aged between 7 and 20 years old who formed the T1DM study group and 40 healthy subjects with similar demographic characteristics to the control group. The patients underwent comprehensive ophthalmic examination and OCT imaging using a Retina Wide protocol (6 × 6 mm). We analyzed the following microvascular retinal parameters: FAZ area, perimeter and circularity and superficial capillary plexus (SCP) and deep capillary plexus (DCP) vessel density. Results: Statistically significant differences between the two groups were identified for the following parameters: the mean FAZ area at follow-up (0.38 ± 0.13) was larger than the mean FAZ area at baseline (0.31 ±0.11), the mean FAZ perimeter at follow-up (3.22 ± 0.75) was larger than the mean FAZ perimeter at baseline (2.61 ± 00.52) and the men FAZ circularity index at follow-up (0.47 ± 0.13) was decreased compared to the FAZ circularity index at baseline (0.56 ± 0.12). A statistically significant difference were also registered for the following parameter: the total SCP and DCP vessel density was decreased at follow-up (37.47 ± 1.57) compared to baseline (38.79 ± 1.00). Conclusions: OCTA long-term monitoring of T1DM patients represents an effective method for tracking progressive changes in FAZ parameters and capillary plexus vascular density.